Causal mechanism of injection-induced earthquakes through the Mw 5.5 Pohang earthquake case study - I. W. Yeo (Nature Portfolio, 2020)
The authors here suggest a causal mechanism for injection-induced earthquakes. They further suggest pore pressure modeling as a practical alternative to direct in-situ pore pressure observation which can then be used for stress build-up monitoring.